Investigating the influence of institutions, politics, organizations, and governance on the COVID-19 response in British Columbia, Canada: a jurisdictional case study protocol - Laura Jane Brubacher; Md. Zabir Hasan; Veena Sriram; Shelly Keidar; Austin Wu; Michael Cheng; Chris Y. Lovato; U. B. C. Working Group on Health Systems Response to COVID-19; Peter Berman (BMC, 2022)
Abstract Background Research on public health responses to COVID-19 globally has largely focused on understanding the virus' epidemiology, identifying interventions to curb transmission, and assessing the impact of interventions on outcomes. Only recently have studies begun to situate their findings within the institutional, political, or organizational contexts of jurisdictions. Within British Columbia (BC), Canada, the COVID-19 response in early 2020 was deemed highly coordinated and effective overall; however, little is understood as to how these upstream factors influenced policy decisions. Methods Using a conceptual framework we developed, we are conducting a multidisciplinary jurisdictional case study to explore the influence of institutional (I), political (P), organizational (O), and governance (G) factors on BC's COVID-19 public health response in 2020-2021. A document review (e.g. policy documents, media reports) is being used to (1) characterize relevant institutional and political factors in BC, (2) identify key policy decisions in BC's epidemic progression, (3) create an organizational map of BC's public health system structure, and (4) identify key informants for interviews. Quantitative data (e.g. COVID-19 case, hospitalization, death counts) from publicly accessible sources will be used to construct BC's epidemic curve. Key informant interviews (n = 15-20) will explore governance processes in the COVID-19 response and triangulate data from prior procedures. Qualitative data will be analysed using a hybrid deductive-inductive coding approach and framework analysis. By integrating all of the data streams, our aim is to explore decision-making processes, identify how IPOG factors influenced policy decisions, and underscore implications for decision-making in public health crises in the BC context and elsewhere. Knowledge users within the jurisdiction will be consulted to construct recommendations for future planning and preparedness. Discussion As the COVID-19 pandemic evolves, governments have initiated retrospective examinations of their policies to identify lessons learned. Our conceptual framework articulates how interrelations between IPOG contextual factors might be applied to such analysis. Through this jurisdictional case study, we aim to contribute findings to strengthen governmental responses and improve preparedness for future health crises. This protocol can be adapted to and applied in other jurisdictions, across subnational jurisdictions, and internationally.